A new species of Germainiella (Bacillariophyta) from the Myristica swamps of the Western Ghats, India. Issue 3 (3rd July 2019) - Thacker, Mital; Roy, Surajit; Kociolek, John Patrick; Lowe, Rex L.; Karthick, Balasubramanian
Abstract : Germainiella chandranii sp. nov. is described from a Myristica swamp of the Western Ghats, India, on the basis of light and scanning electron microscopy. The new species resembles two related genera, Fallacia Stickle & D.G. Mann and Germainiella Lange–Bertalot & Metzeltin on the basis of valve morphology, but a thorough investigation of valve ultrastructure confirms its placement in Germainiella. External valve outline and morphology, large conopeum covering the entire face of the valve, siliceous struts running perpendicular to the raphe support the generic assignment. The main diagnostic features of the new species are the presence of small tubules running perpendicular to the raphe, striae composed of a series of round to elongated areolae, which are not covered internally by hymenes, and a larger central area. The new species occurs in acidic waters of the Myristica swamps of the Western Ghats and it can be considered as an indicator of the acidic condition.